Sustainable upcycling of sugarcane bagasse into nanofibrillated cellulose utilizing novel green solvents and high intensity ultrasonication - Pandey A.; Kalamdhad A.S.; Sharma Y.C. (My University, 2025)
Nanofibrillated cellulose (NFC) are versatile materials with applications spanning from advanced composites to water treatment innovations. Production of NFC using biopolymers found in agricultural waste residues holds importance due to their environmentally friendly nature, providing viable substitute for non-renewable petroleum resources. From the perspective of sustainable economy, this article focuses on utilizing agricultural waste, sugarcane bagasse (SCB) for the production of nanofibrillated cellulose using green approach. Here, we synthesized four different types of acidic natural deep eutectic solvents (NADES) and investigated their potential as pretreatment agents synergistically with acetosolv, aiming to enhance cellulose recovery from SCB. The pretreatment step led to significant yield of cellulose (84.4 %) using Gly-CA NADES and acetosolv combination. The yields in case of Xyl-CA (82.2 %), Gly-TA (75.6 %) and Xyl-TA (68.9 %) were relatively lower. Subsequent implementation of high-intensity ultrasonication (HIU) process resulted in rapid nanofibrillation of fibres with minimal cellulose loss. The morphological and particle size analyses of the produced NFC samples using SEM, TEM and DLS revealed that they exhibited heterogeneity with lengths varying from 25 to 80 nm and widths varying from 5 to 10 nm, indicating a high efficiency of disintegration. The qualitative analysis of NFCs was also investigated by employing XRD, FTIR and TGA/DTG that further determined that the structure of NFCs remained unaltered even after subjecting it to various treatment methods. Thus, the study signifies a holistic approach to resource recovery and promoting sustainable and environmentally friendly biomass conversion processes. © 2023 Elsevier B.V.